Research and application of new method based on MDT intelligent analysis of LTE radio interference - Zhong, Qizhu; Wu, Xiuquan; Luo, Yaoman (Dianxin Kexue, 2019)
Aiming at the traditional LTE(long term evolution) wireless interference judgment analysis method has insufficient user dimension data, insufficient correlation of quality reasons, and too much dependence on manual analysis.A new method based on MDT(minimized drive test) technology for intelligent analysis of LTE radio interference was proposed. Firstly, the user's wireless quality data and latitude and longitude information were collected by using MDT and MR(measurement report), and then DBSCAN(density-based spatial clustering of applications with noise) and adaptive clustering algorithm were used to collect the wireless coverage indicators and the latitude and longitude and other data were used for cluster analysis. Finally, the clustered data was imported into the self-built wireless interference judgment model, and the interference type was analyzed to realize the intelligent analysis of LTE wireless interference. Compared with the traditional interference analysis method, the proposed method can avoid th